PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN PLATFORM LUMIO BY SMART UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SMP NEGERI 40 SURABAYA - Intan Maulina, Safira; Agus Sutedjo; Pras Setyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problem currently being faced in social studies learning for class IX-E of SMP Negeri 40 Surabaya is that 17 out of 31 students or around 54.83% (fifty four point eighty three percent) of students have not reached the Learning Goal Achievement Criteria (KKTP). So this has a continuous impact on students' knowledge and hampers the process of achieving classical completion. So this research was carried out with the aim of improving the learning outcomes of class IX E students at SMP Negeri 40 Surabaya through the application of the Problem Based Learning (PBL) learning model which is supported by the Lumio by Smart digital learning platform. This Classroom Action Research (PTK) was carried out in two cycles, each of which consisted of planning, implementation, observation and reflection stages. The research results showed a significant increase in student learning outcomes. In the pre-cycle, the average learning outcome reached 60.32 with classical completeness of 45.16%. After implementing the first cycle, the average learning outcome increased to 74.67 with classical completeness of 58.06%. In the second cycle, learning outcomes increased more significantly with an average of 85.48 and classical completeness reached 93.54%. The conclusion of this research is that the application of the PBL model supported by Lumio by Smart effectively improves student learning outcomes, as well as having a positive impact on their involvement and motivation in the learning process.